An Epidemiological Meta-Analysis on the Worldwide Prevalence, Resistance, and Outcomes of Spontaneous Bacterial Peritonitis in Cirrhosis - Tay, Phoebe Wen Lin; Xiao, Jieling; Tan, Darren Jun Hao; Ng, Cheng; Lye, Yan Nerng; Lim, Wen Hui; Teo, Vanessa Xin Yi; Heng, Ryan Rui Yang; Yeow, Marcus Wei Xuan; Lum, Lionel Hon Wai; Tan, Eunice Xiang Xuan; Kew, Guan Sen; et al. (Frontiers in Medicine, 2021)
Background and Aims: Spontaneous bacterial peritonitis (SBP) is a common and potentially fatal complication of liver cirrhosis. This study aims to analyze the prevalence of SBP among liver cirrhotic patients according to geographical location and income level, and risk factors and outcomes of SBP. Methods: A systematic search for articles describing prevalence, risk factors and outcomes of SBP was conducted. A single-arm meta-analysis was performed using generalized linear mix model (GLMM) with Clopper-Pearson intervals. Results: 99 articles, comprising a total of 5,861,142 individuals with cirrhosis were included. Pooled prevalence of SBP was found to be 17.12% globally (CI: 13.63% - 21.30%), highest in Africa (68.20%; CI: 12.17% - 97.08%), and lowest in North America (10.81%; CI: 5.32% - 20.73%). Prevalence of community-acquired SBP was 6.05% (CI: 4.32% - 8.40%), and 11.11% (CI: 5.84% - 20.11%,) for healthcare-associated SBP. Antibiotic-resistant microorganisms were found in 11.77% (CI: 7.63% - 17.73%) of SBP patients. Of which, methicillin-resistant Staphylococcus aureus was most common (6.23%; CI: 3.83% – 9.97%), followed by extended-spectrum beta-lactamase producing organisms (6.19%; CI: 3.32% - 11.26%), and lastly vancomycin-resistant enterococci (1.91%; CI: 0.41% - 8.46%). Subgroup analysis comparing prevalence, antibiotic resistance and outcomes between income groups was conducted to explore a link between socioeconomic status and SBP, which revealed decreased risk of SBP and negative outcomes in high-income countries. Conclusion: SBP remains a frequent complication of liver cirrhosis worldwide. The drawn link between income level and SBP in liver cirrhosis may enable further insight on actions necessary to tackle the disease on a global scale.